Revisiting Extracellular RNA Release, Processing, and Function. Issue 6 (June 2021) - Tosar, Juan Pablo; Witwer, Kenneth; Cayota, Alfonso
Abstract : It is assumed that RNAs enriched in extracellular samples were selected for release by their parental cells. However, recent descriptions of extracellular RNA (exRNA) biogenesis and their differential stabilities question this assumption, as they could produce identical outcomes. Here, we share our opinion about the importance of considering both selective and nonselective mechanisms for RNA release into the extracellular environment. In doing so, we provide new perspectives on RNA-mediated intercellular communication, including an analogy to communication through social media. We also argue that technical limitations have restricted the study of some of the most abundant exRNAs, both inside and outside extracellular vesicles (EVs). These RNAs may be better positioned to induce a response in recipient cells compared with low abundance miRNAs. Highlights: A significant proportion of extracellular RNAs (exRNAs) are not associated with extracellular vesicles (EVs). Small exRNAs can be generated in the extracellular space from longer precursors like tRNAs and ribosomes. The biogenesis of exRNA coupled to differential stability destroys positive correlations between intracellular and extracellular RNA profiles. Contamination with cell culture additives is also a source of RNAs that appears to be enriched in extracellular samples. Abundant RNA species, such as full-length tRNAs, are also abundant inside EVs.